Melatonin inhibits GnRH-induced Ca2+ mobilization and influx through voltage-regulated channels - Slanar, O; Zemkova, H; Vanecek, J (Biological signals, 1997)
In neonatal rat gonadotrophs, melatonin acts through the high-affinity membrane-bound receptors to inhibit GnRH-induced [Ca2+]i increase. GnRH increases [Ca2+]i primarily by mobilization from the inositol trisphosphate-sensitive pool followed by Ca2+ influx through the voltage-sensitive channels. Melatonin inhibits the GnRH-induced [Ca2+]i increase. When added after the GnRH-induced spike, melatonin decreases [Ca2+]i in 52% of the gonadotrophs. The effect of melatonin is dependent on extracellular Ca2+ and may be mimicked by Ca2+-free medium or verapamil. When added before GnRH, melatonin inhibits the [Ca2+]i spike. This effect of melatonin is independent of extracellular Ca2+ as it persists in Ca2+-free medium. These findings indicate that melatonin blocks Ca2+ mobilization as well as Ca2+ influx in the gonadotrophs.
Keywords: Calcium; Calcium Channels; Ion Channel Gating; gating iontového kanálu; melatonin; Gonadotropin-Releasing Hormone; vápník; hormon uvolňující gonadotropiny; novorozená zvířata; Female; krysa rodu Rattus; zvířata; Cells, Cultured; potkani Wistar; Animals, Newborn; Pituitary Gland, Anterior; ženské pohlaví; Rats, Wistar; kultivované buňky; adenohypofýza; vápníkové kanály; Rats; Animals; Melatonin